The best way to the trap: An ecological study of coffee berry borer (Hypothenemus hampei) preference to several volatile compounds - Kurnianto, Agung Sih; Haryadi, Nanang Tri; Dewi, Nilasari; Pamungkas, A. S. P.; Magvira, Nur Laila; Septiadi, Luhur (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2024)
This study explored the effectiveness of ethanol and methanol as attractants for controlling the coffee berry borer (CBB), Hypothenemus hampei Ferr 1867, a significant pest in global coffee plantations. The research aimed to assess the efficiency of these substances as attractant traps for CBB in Kaliselogiri, Banyuwangi, Indonesia. Using a single-factor randomized block design, the experiment involved nine treatments, each replicated three times, with modified PTE traps of 2 L volume set up at 1.5 m height. Traps were checked weekly to monitor CBB attack intensity before and after applying attractants. Statistical analyses including the Mann-Whitney Non-parametric test and Duncan’s test were used to examine variations across blocks and weeks. Abundance boxplot graphs offered descriptive insights. Over six weeks, 14,044 CBB’s were captured. The peak was in the third week, with a decline in the fourth, followed by a resurgence until the end of the study. The Mann-Whitney U test showed a significant p-value (p = 0.000; confidence level = 5%), confirming the effectiveness of the attractants on CBB. Of the treatments, K6 (Ethanol: Methanol = 2:1) was most effective. Ethanol and methanol proved to be efficient lures in CBB management traps, with ethanol particularly effective in larger compositions, suggesting its wider application. These results support the use of attractant-based strategies for CBB control and highlight the importance of ethanol and methanol. Further research is needed to optimize attractant compositions and assess long-term impacts on CBB populations and agroecosystems. The ecological consequences, including potential effects on non-target species and overall sustainability, warrant further investigation. In summary, this study advances CBB management through attractant-based traps, emphasizing the importance of ethanol.